2006
DOI: 10.1111/j.1467-6486.2006.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Globalfocusing: From Domestic Conglomerates to Global Specialists*

Abstract: Globalization is changing the competitive terrain on which companies develop their corporate strategy. On the global stage, key competitive advantages are gained through internationally fungible resources. Consequently, diversified conglomerates are converting to global specialists in narrower niche markets and competing with a small number of multinational enterprises operating worldwide. Their internationalization and their reduction of product diversification are opposite sides of the same coin: globalfocus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 86 publications
(136 reference statements)
3
107
1
Order By: Relevance
“…In consequence, Danisco sold its erstwhile largest business unit, Danisco Sugar, in March 2009 to focus entirely on food ingredients. Many major European conglomerates restructured in a similar direction, though rarely as radical as in these two case examples (Meyer, 2009 (Meyer, 2006). Globalisation has created an integrated competitive landscape, where (almost) every firm competes with any other firm that happens to offer similar products or services.…”
Section: Globalfocusingmentioning
confidence: 99%
See 1 more Smart Citation
“…In consequence, Danisco sold its erstwhile largest business unit, Danisco Sugar, in March 2009 to focus entirely on food ingredients. Many major European conglomerates restructured in a similar direction, though rarely as radical as in these two case examples (Meyer, 2009 (Meyer, 2006). Globalisation has created an integrated competitive landscape, where (almost) every firm competes with any other firm that happens to offer similar products or services.…”
Section: Globalfocusingmentioning
confidence: 99%
“…The shift from domestic to global growth paths in the past three decades has been driven by shifts in barriers to entry across industries and countries due to the globalisation of markets, resources, supply chains and business models (Meyer, 2006). These global strategies, operations and resources position MNEs them quite differently than during earlier recessions.…”
Section: Introductionmentioning
confidence: 99%
“…Globalization is changing ways of doing business (O'Donnell, 2000) and the competitive environment in which companies carry out their corporate strategies (Meyer, 2006). Multinational companies (MNCs) are the main proponents of growing economic interdependence between nations and regions, which has transformed them into "key actors in the globalization process" (Rugman and Verbeke, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, as mentioned by Yiu et al (2007), there is a paucity of research associated with the internationalization of business groups. While several of the benefits provided by diversified business groups seems to be location-bound (Tan and Meyer, 2010;Meyer, 2006), empirical evidence is not conclusive about the impact of diversified business groups on the internationalization of their affiliates.…”
Section: Managing the Complexities Of Internationalization: Assessingmentioning
confidence: 99%
“…However, Meyer (2006) suggested that knowledge of institutional systems and links with government officials are specific to a particular country.…”
Section: Business Group Diversification and Firm Performancementioning
confidence: 99%